New challenges for future sustainability and wellbeing - Özen, Ercan; Grima, Simon; Dalli Gonzi, Rebecca (Emerald Publishing Limited, 2021)
Our current economic systems have become addicted to growth at all costs, as measured by Gross Domestic Product (GDP). They assume that GDP growth is synonymous with increased wellbeing and prosperity. However, this approach has led to growing inequality, an escalating climate crisis, and the depletion of natural and social capital. Our approach to economics and development needs to be fundamentally transformed. New Challenges for Future Sustainability and Wellbeing is a collection of 25 studies about sustainability and the related challenges, such as income, wealth, social aspects, the environment, education and regional equality that influence the pace of economic development and deteriorates well-being of people and organisations all over the world. This book provides a platform for scholars, researchers and professionals from different disciplinary backgrounds to discuss, highlight and exchange ideas on these challenges and prospects for both economic and business development.- Resumé vydavatel
Includes index.
Keywords: kvalita života; quality of life; elektronické knihy; sborníky; electronic books; papers of several authors